The loan puzzle in Mexico - Luis Fernando Colunga-Ramos (Latin American Journal of Central Banking (LAJCB), 2025)
Empirical evidence for advanced economies suggests that following a monetary tightening, commercial and industrial bank loans show a positive "puzzling response". Since there is no wide evidence for the Mexican case, this paper analyzes the response of bank loans at the sectoral level after a monetary contraction. For this purpose, I estimate a structural VAR model with block exogeneity to identify a monetary shock for a small open economy. The results show evidence of firms' loan puzzles during 2001-2019 characterized by an inflation-targeting regime in Mexico. Those short-lived loan puzzles are mainly observed in sectors with the lowest delinquency rates during the period of analysis. My finding of the loan puzzle at the aggregate level in a recent sample arises in a closed as well as in an open economy approach.
Keywords: E51; E52; E58; 330; Bank lending channel; Loan puzzle; Monetary policy shocks; SVAR